Phosphorus Dynamics Near Bald Cypress Roots in a Restored Wetland - Moorberg, Colby J.; Vepraskas, Michael J.; Niewhoener, Christopher P. (My University, 2017)
Core Ideas Previous tree exposure to saturated conditions limited root death after ponding. Root growth and death had no apparent effect on concentrations of Fe2+, DOC, or DTP. Concentrations of Fe2+ were related to water table levels and redox status. Phosphorus concentrations were controlled by iron reduction and oxidation. Phosphorus (P) dissolution occurs commonly in wetland soils restored from agricultural land. Associated with P release are high concentrations of dissolved organic carbon (DOC) and Fe2+. This field study evaluated the effect of a fluctuating water table on the root dynamics of bald cypress (Taxodium distichum L. Rich.) to determine whether root death created soil reduction microsites, potentially contributing to P dissolution. The study site is a restored Carolina bay wetland with organic soils. Root growth and death were monitored on 16 6-yr-old bald cypress using minirhizotrons. Root dynamics, water table levels, and soil porewater chemistry and redox potential in the root zone were monitored for 2 yr. Soil solution samples were analyzed for Fe2+, pH, DOC, and P. High rates of root growth occurred during dry conditions, whereas root death occurred during sustained periods of saturation, particularly within 20 cm of the surface. Cyclic changes in concentrations of Fe2+, DOC, and dissolved total P (DTP) were related to water table position but not to changes in root numbers. After sustained periods of saturated conditions, redox potential decreased to 0 mV, Fe2+ increased to 1.75 mg Fe2+ L–1, and DOC increased to 350 mg L–1, resulting in peak DTP concentrations of 750 μg L–1, compared with 100 μg L–1 during dry periods. This study showed that in these high-C soils (∼20% organic C) rooting dynamics had minimal impact on changes in P concentrations and that P dissolution was largely controlled by Fe reduction processes occurring within the C-rich soil matrix.